2006
DOI: 10.1097/01.prs.0000210681.90799.b1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Differentiation and Localization Analysis of Sweat Glands in the Adult Human Axilla

Abstract: In the authors' Caucasian subjects, all or most of the sweat glands were found in the subcutaneous tissue near the border to the dermis and not in the dermis. For extremely hyperfunctioning sweat glands, the authors recommend less radical surgical methods, with the preservation of skin, based on the knowledge that most glands are localized in the subcutaneous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Serial sections of axillary skin from hyperhidrosis and healthy control subjects were analysed to detect the presence of apoeccrine glands using immunocytochemical markers supposedly specific to this gland type (13)(14)(15). Gland measurements in control and hyperhidrosis patients were taken using image analysis to identify any obvious morphological changes associated with gland hypertrophy and to provide additional morphological identification of the different gland types.…”
Section: Experimental Designmentioning
confidence: 99%
“…Serial sections of axillary skin from hyperhidrosis and healthy control subjects were analysed to detect the presence of apoeccrine glands using immunocytochemical markers supposedly specific to this gland type (13)(14)(15). Gland measurements in control and hyperhidrosis patients were taken using image analysis to identify any obvious morphological changes associated with gland hypertrophy and to provide additional morphological identification of the different gland types.…”
Section: Experimental Designmentioning
confidence: 99%
“…These complications may result from the surgical technique itself, which aims for an excessive ablation of sweat glands after dissecting fat from the dermis, with subsequent alteration of the dermal and subcutaneous blood vessels. Thus, general agreement exists in the literature that after LC, the axillary operated skin should be similar to a full-thickness skin graft with additional blood supply from the surrounding nonoperated skin [5]. However, although this consensus has been reached, and LC has become a popular and frequent technique, the status of microcirculation and blood flow of axillary skin before and after LC has not been investigated until today.…”
Section: Discussionmentioning
confidence: 93%
“…If these nonresponders desire permanent reduction of sweating, surgical options should be considered, ranging from removal of subcutaneous tissue without skin excision to resection of axillary skin with adjacent subcutaneous tissue to a combination of both methods, resulting in a partial skin resection with combined removal of subcutaneous and surrounding tissue [17]. Both – the anatomical location of human sweat glands and clinical studies evaluating surgical techniques – have resulted in a preference for minimally invasive strategies for treating FAH [1,2,3,4,5, 18, 19]. LC has demonstrably reduced the sweat rate significantly with a low risk of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the suction should be in the right skin layer. As histologic studies [13] have shown that all or most of the Ugly looking (axillae %) 5 1/130 axillae (0.77 %) 27/130 axillae (20.77 %) 1 The experimental group has statistically significant higher incidence of total satisfaction. (p value = 0.004, Chi-square test) 2 The experimental group has statistically significant lower incidence of skin necrosis.…”
Section: Discussionmentioning
confidence: 97%